MENINGKATKAN HASIL BELAJAR IPA MELALUI COOPERATIF LEARNING TIPE TEAM GAMES TOURNAMENT DI KELAS V SD NEGERI 101855 KUTALIMBARU - Syarifah Ainun Harahap (Pragmatik: Jurnal Ilmiah Ilmu Pendidikan, 2024)
This study aims to improve the science learning outcomes of students Team Games Tournament.This type of research is classroom action research. The subjects of this study were students of class V Negeri 101855 Kutalimbaru, totaling 28 students, consisting of 13 male students and 15 female students. Researchers used an action research model from Kemmis and Taggart. This research was conducted in two cycles of action. In the first cycle, it was conducted in one meeting, while in the second cycle, it was conducted in two meetings. In each cycle, there are planning, implementation, observation and reflection activities. The instruments used were observation sheets and tests. Observation data were analyzed descriptively qualitatively while test results were analyzed descriptively quantitative percentage.The results of the first cycle research showed that the percentage of students whose grades were above the KKM had only reached 71.43%, so they still could not achieve the criteria for research success. In cycle II, the steps for applying the Team Games Tournament method to improve student success were carried out. The percentage of student scores above the KKM in cycle II increased to 89.29%. Based on the research results, it can be seen that the guided survey method can improve science learning outcomes.